Spirulina breath test indicates differences in gastric emptying based on age, gender, and BMI. Issue 6 (23rd January 2021) - Orsagh‐Yentis, Danielle K.; Bai, Shasha; Bobbey, Adam; Hayes, Caitlin; Pusateri, Antoinette; Williams, Kent
Abstract: Background: Measurements of gastric emptying (GE) by scintigraphy in the pediatric population are based on adult standards. Due to radiation exposure, scintigraphy cannot be performed on healthy children to establish norms of GE in the pediatric population. Stable isotope breath tests (GEBTs) pose no such health risk to children. This study sought to determine the feasibility of a GEBT in children and to investigate whether GE may differ by age, gender, or body mass index (BMI). Methods: Fifty healthy children 6 to 18 years underwent a 13 C‐Spirulina platensis GEBT. Breath samples were obtained at baseline, every 15 min for 1 h, and at 30‐min intervals for 3 h thereafter. Seventeen similarly aged patients with dyspeptic symptoms concurrently underwent scintigraphy and the GEBT. Key Results: Forty‐six healthy subjects were included in the final analysis. Females had an overall slower rate of GE than did males. At nearly all timepoints, children with a BMI >85 th percentile had slower GE than normally weighted children. The GE rate of children aged 6–9 reached a maximum later than did the rate of older children. Thirteen patients undergoing scintigraphy were included in the comparative analysis. The agreement between scintigraphic and GEBT half‐times as measured by the concordance correlation coefficient was 0.383 (95% CI: 0.02–0.65). Conclusions and Inferences: GEBT was easily accomplished in healthy children. Differences of GE rates by age, gender, and BMI support the need for establishing pediatric standards of GE. One way to establish such standards may be through the use of a GEBT. Abstract : The Spirulina gastric emptying breath test is feasible in children. In our study, the breath tests of healthy children 6‐18 years of age revealed demographic differences in gastric emptying. Young children achieved peak emptying later than did older children; females had slower rates of gastric emptying than did males; and overweight children had slower rates of gastric emptying than children of normal weight. These are predicted values of the 13 CO2 excretion rate following the restrictive cubic spline model separated by (A) age group, adjusting for gender and BMI, (B) gender, adjusting for age and BMI, and (C) overweight status, adjusting for age and gender.